Pengaruh Motivasi Belajar dengan Teman Sebaya pada Minat untuk Melanjutkan Pendidikan ke Perguruan Tinggi pada Siswa dan Siswi SMKN 1 Bojonggenteng - indah, indah purnamasari (Nusa Putra University, 2020)
This study aims to determine whether learning motivation and peers affect class XII students of SMKN 1 Bojonggenteng class 2019/2020 to continue to college. The data collection process was carried out by means of a questionnaire, while the data analysis used multiple regression analysis. From the results of this study, it can be seen that: (1) learning motivation has a positive effect on interest in continuing to study, (2) peers have a positive effect on interest in continuing college, (3) learning motivation, and peers have a positive effect on interest in continuing to study. higher education.